2015
DOI: 10.1021/jp511758w
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Sources of the Apparent Irreproducibility of Amyloid Formation: Drastic Changes in Kinetics and a Switch in Mechanism Due to Micellelike Oligomer Formation at Critical Concentrations of IAPP

Abstract: The aggregation of amyloidogenic proteins is infamous for being highly chaotic, with small variations in conditions sometimes leading to large changes in aggregation rates. Using the amyloidogenic protein IAPP (islet amyloid polypeptide protein, also known as amylin) as an example, we show that a part of this phenomenon may be related to the formation of micellelike oligomers at specific critical concentrations and temperatures. We show that pyrene fluorescence can sensitively detect micellelike oligomer forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
89
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(103 citation statements)
references
References 96 publications
13
89
1
Order By: Relevance
“…2c). Characteristic but not exclusive of HEWL aggregation, the low reproducibility of the results further prevents definitive conclusions to be made without testing wider ranges of protein concentrations and numerous other replicates (40,43,47,48). The previously reported formation of intermediate and off-pathway species during amyloid fibrillization of lysozyme should, however, produce atypical kinetic signatures and explain in part the poor reproducibility indexes.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…2c). Characteristic but not exclusive of HEWL aggregation, the low reproducibility of the results further prevents definitive conclusions to be made without testing wider ranges of protein concentrations and numerous other replicates (40,43,47,48). The previously reported formation of intermediate and off-pathway species during amyloid fibrillization of lysozyme should, however, produce atypical kinetic signatures and explain in part the poor reproducibility indexes.…”
Section: Resultsmentioning
confidence: 91%
“…A striking result not covered by any of the scenarios in Fig. 1b is the weak dependence of the lag time on concentration with absolute values of ␥ well below 1 at high monomer concentrations (15,31,40,43). In the case of lysozyme aggregation under harsh denaturating conditions, the process becomes nearly concentration-independent (␥ Ӎ 0) for protein concentrations significantly higher than the solubility (40).…”
mentioning
confidence: 94%
“…60 Previous ssNMR studies have shown α-helical structures of Amylin and not cross-β structure. 61,62 Recent ssNMR studies presented unstructured Aβ oligomers 63 and Amylin oligomers that form large micelles, 64 which may be a general phenomenon for natively unstructured Amylin. We did not apply these α-helical and the unstructured amylin, or the unstructured Aβ oligomers in the current study, because of the lack of the PDB coordinates.…”
Section: Resultsmentioning
confidence: 99%
“…Human-IAPP forms “micelle-like” mesoscopic aggregates whereas the rat-IAPP does not [90]. It is also reported that micelle formation correlated with amyloidogenicity of the peptide: the naturally-occurring C-amidated human-IAPP exhibited about 10 times less CMC than the non-amidated while the human-IAPP-1–19 fragments of both human and rat did not form micelles [109]. Studies have shown that the presence of lipid influences the aggregation of IAPP [86,9398,117125].…”
Section: Protein Aggregation and Amyloid Formation In A Membrane Envimentioning
confidence: 99%